Pemberdayaan Masyarakat dalam Pengelolaan Limbah Bonggol Jagung dan Buah Pinus Menjadi Briket sebagai Energi Berkelanjutan: Penelitian - Andhika Lungguh Perceka, Andhika Lungguh Perceka; Elang Mohamad Atoilah, Elang Mohammad Atoilah; N. Ai Erlinawati, N. Ai Erlinawati (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Sindanggalih Karangpawitan Village is an area with high agricultural activity, especially in corn cultivation and pine plantations. Corn production generates corn cob waste that has not been optimally utilized, while abundant pine nuts also have the potential as raw material for briquettes. The implementation method used is an approach and application of technology. The results obtained show that residents' knowledge of processing waste from corn cobs and pine nuts has increased, and residents have the ability to process waste and are able to use technology for the processing. From this activity, it can be concluded that the residents of RW 15 have understood and are able to process corn cobs and pine nuts into briquettes as sustainable energy. In addition, a community business group called the independent green energy group has been formed to continue the briquette processing business. This community service activity has opened up new business opportunities and provided an alternative energy source that can be used by the community in their daily lives.